Wetland degradation and conservation of natural resources in haor areas: a study at Tahirpur and Dharmapasha upazilas of Shunamganj district - Azmery, Shah Israt; Kabir, Md Humayun; Bhuiyan, Md Ferdous-ur-Rahman (Journal of the Asiatic Society of Bangladesh, Science, 2023)
The study investigates the issues concerning wetland degradation and analyzes the conservation and management initiatives of natural resources in the study area. Using both quantitative and qualitative methods, primary data were collected from two selected upazilas (Tahirpur and Dharmapasha) of the Sunamganj district. For the survey, 150 households were selected in 9 villages. Four focus group discussions and 8 key informant interviews were also carried out. Data from the landsat satellite images have been analyzed using the NDWI and the supervised image classification approach. The study results demonstrate that the deep water area in Dharmapasha and Tahirpur upazila have declined by more than 17 km2, and 26 km2, respectively, between 1989 and 2019. In addition, due to overexploitation and mismanagement, the wetland resources have been greatly reduced, leading to degradation. However, the conservation of natural resources in the study area faces many challenges due to lack of proper management practices. J. Asiat. Soc. Bangladesh, Sci. 49(1): 71-83, June 2023